2002
DOI: 10.1051/0004-6361:20020690
|View full text |Cite
|
Sign up to set email alerts
|

Opacity in the upper atmosphere of AU Mic

Abstract: Abstract. In this paper we investigate the validity of the optically thin assumption in the transition region of the late-type star AU Mic. We use Far-Ultraviolet Spectroscopic Explorer (FUSE) observations of the C  multiplet and O  resonance lines, hence yielding information at two different levels within the atmosphere. Significant deviations from the optically thin fluxes are found for C  in both quiescent and flare spectra, where only 60% of the flux is actually observed. This could explain the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…As reported in previous publications of these data sets, AD Leo shows two distinct flares (Christian et al 2006), AU Mic (Bloomfield et al 2002) shows one flare, and AB Dor (Dupree et al 2006) shows three flares, two of which appear during observational day-time and are therefore not considered for further analysis. In Fig.…”
Section: Lightcurve Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…As reported in previous publications of these data sets, AD Leo shows two distinct flares (Christian et al 2006), AU Mic (Bloomfield et al 2002) shows one flare, and AB Dor (Dupree et al 2006) shows three flares, two of which appear during observational day-time and are therefore not considered for further analysis. In Fig.…”
Section: Lightcurve Analysismentioning
confidence: 96%
“…Dupree et al (1976) found that the ratio is enhanced for active solar regions. On stars, this ratio was found to be enhanced during flaring (Bloomfield et al 2002;Christian et al 2006). The C iii(λ977 Å) transition region A&A 536, A62 (2011) Notes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As in our previous work (Bloomfield et al 2002;Christian et al 2004Christian et al , 2006 we measured emission line fluxes by fitting Gaussians to the observed line profiles. In general, a single Gaussian profile was sufficient to fit both the O vi transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence deviations of the observed line ratio from the optically thin value allows the optical depth and hence parameters of the emitting plasma to be derived. Using this method, several studies have found TR scale heights between 10-100 km for active stars including AU Mic (Bloomfield et al 2002), the flare star Prox Cen (Christian et al 2004) and AD Leo (Christian et al 2006). …”
Section: Introductionmentioning
confidence: 99%